Exploring challenges of women doctoral students: a conceptual paper - Tan, Celine Choe Chai; Zakaria, Noor Syamilah (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
Many studies have shown that women in many countries obtained Bachelor and Master’s levels in greater numbers than men; nonetheless, they are less likely to proceed further to doctorate level. As women, they are expected to bear more responsibilities for family duties rather than excel in academic achievements. There are various challenges that exist for women to complete a doctorate study: academic tasks, domestic demands, financial constraint, anxiety as well as lack of personal, family, career and academic life balance. In addition, multiple workloads, time constraint and future career uncertainty have also cause an extremely high level of stress. Age is another common dilemma for many women doctorate students. Some married women would delay motherhood in pursuit of their studies but consequently may affect their ability to bear children at later age. It is even more challenging when they enter motherhood as there are always unequal expectations of the maternal roles. Unfortunately, when the women doctorate students voice their concerns on the challenges they face, they often receive negative advice or discouragement from families and friends due to the society has lower expectation for women to achieve tertiary education. Majority of past research on women doctorate students found that their life is full of academic and emotional challenges which can affect their family relationships negatively. Hence, there is a need to conduct a study to further understand the in-depth experience of women doctorate students in achieving their academic goals, career progression and life balance while fulfilling their doctorate endeavour.